2022
DOI: 10.1111/petr.14324
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and incidence of cytomegalovirus viremia and disease in pediatric patients with allogeneic hematopoietic stem cell transplantation: An 8‐year single‐center experience in Latin America

Abstract: Background: Cytomegalovirus infection represents a significant cause of morbidity and mortality after hematopoietic stem cell transplantation. This study aimed to evaluate the incidence of viremia and disease due to cytomegalovirus and the risk factors in pediatric patients with hematopoietic stem cell transplantation in our institution. Methods: This was a retrospective cohort of patients under 19 years of age who underwent allogeneic hematopoietic stem cell transplantation due to any indication between 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Our result was quite similar to a current study in which the cumulative incidences of CMV DNAemia in the MSD, MUD and haploidentical groups were 39.0, 55.6, and 85.7%, respectively ( Lin et al., 2019 ). Another retrospective pediatric patient study from a single center in Latin America showed that the cumulative incidence of CMV viremia was 70.5% while CMV disease was 4.7% ( Aristizabal et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our result was quite similar to a current study in which the cumulative incidences of CMV DNAemia in the MSD, MUD and haploidentical groups were 39.0, 55.6, and 85.7%, respectively ( Lin et al., 2019 ). Another retrospective pediatric patient study from a single center in Latin America showed that the cumulative incidence of CMV viremia was 70.5% while CMV disease was 4.7% ( Aristizabal et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies ( Ganepola et al., 2007 ; Schmidt-Hieber et al., 2013 ; Takenaka et al., 2015 ), we have not identified the CMV serostatus of donor and recipient as a significant factor, which might result from the existing unknown data. Eventually, it was well established that CMV infection was associated with overall mortality especially CMV disease ( Rowe et al., 2016 ; Aristizabal et al., 2022 ; Ru et al., 2022 ). Therefore, we recommend that it was required to carefully and rigorously monitor CMV infection after haplo-HSCT in leukemia patients in whom letermovir may be appropriately used for prophylaxis in the future study (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation